Rachel Carson Challenging Authors - Stein, Karen F.; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2012)
Karen F. Stein University of Rhode Island, Kingston, USA Rachel Carson is the twentieth century s most significant environmentalist. Her books about the sea blend science and poetry as they invite readers to share her celebration of the ocean s wonders. Silent Spring, her graphic and compelling exposé of the damage caused by the widespread aerial spraying of persistent organic pesticides such as DDT, opened our eyes to the interconnectedness of all living beings and the ecological systems we inhabit. Carson s work challenges our belief that science and technology can control the natural world, asks us to recognize our place in the world around us, and inspires us to treat the earth respectfully. She calls us to rekindle our sense of wonder at nature s power and beauty, and to tread lightly on the earth so that it will continue to sustain us and our descendants. This book guides readers on a journey through Carson s life and work, considers Carson s legacies, and points to some of the continuing challenges to sustainability. It provides a listing of resources for reading, learning, or teaching about the environment, about nature writing, and about Carson and the crucial issues she addressed.
Keywords: Education; Education; Education (general).